Prevalence and incidence of celiac disease in patients with rheumatoid arthritis: a case-control study based on the RECORD cohort - Sakellariou, Garifallia; Schiepatti, Annalisa; Zanetti, Anna; Montecucco, Carlomaurizio; Biagi, Federico; Scirè, Carlo Alberto (Frontiers in Medicine, 2025)
BackgroundThe reported prevalence of coeliac disease (CD) in rheumatoid arthritis (RA) is variable.ObjectiveTo evaluate the prevalence and incidence of CD in RA and controls.DesignCase-control study on administrative data.MethodsThe RECord linkage On Rheumatic Disease database (administrative data, 2004–2013) was used to retrieve patients with RA and age and sex-matched controls. Prevalence and incidence of CD were calculated and stratified according to age, gender, and calendar year.ResultsThe cohort included 346,956 subjects (mean age 59.9 (14.5), 70.7% females), of which 70,061 RA and 276,895 controls. Median follow-up was 9 years (IQR 9–9). The prevalence of CD was higher in RA (171/70,061 = 0.24% (0.2–0.3%) vs 398/276895 = 0.14% (0.1–0.2%), p < 0.001). The prevalence of CD among females with RA was increased compared to controls (0.3% vs 0.08%, p < 0.001), but was not increased in males with RA. The incidence was higher in RA and remained stable throughout the observation period.ConclusionThe prevalence and incidence of CD were increased in RA, particularly in females.